Saúde mental e bem estar subjetivo dos estudantes de medicina da UFERSA - Silva, Layz Joana da (Universidade Federal Rural do Semi-Árido, 2020)
This work’s objective was to comprehend which are the biological, social and psychological factors which influence the mental health, the mental struggle, the subjective well being and the life of UFERSA’s Medicine students. The research was based on quantitative method, by the use of questionnaires which data were analyzed statistically in a descriptive way, considering frequency, percentage, mean and standard deviation for the sake of the investigation of the data. Test-t Student and ANOVA were used (or equivalent parametric tests). It was possible to know which factors influence the mental health and the subjective well being with greater weight and lesser weight on the Medicine students in the college’s environment , considering general aspects of their lives, spotlighting interpersonal relationships, satisfaction with leisure and sleep, the presence of chronic diseases, stress, sex and others. This work was able to conclude that the data obtained can be used for the further realization of new studies, as well as they can be used for the elaboration of future intervention projects aiming the improvement of the mental health of the medicine students, having an important role for the means of knowledge and prevention in health.
Keywords: Bem-estar subjetivo; Saúde mental; Estudantes de medicina; psicologia; Psiquiatria; Subjective well being; Mental health; Medicine Students; Psychology; Psychiatry; CIENCIAS DA SAUDE::MEDICINA